Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Presipitas Dengan Variasi PH Dan Suhu Sintering - Muhammad Alfin Khairullah; Yelmida Yelmida; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite is a bioceramic acid which is widely used as a bone and tooth graft, catalyst and adsorbent. Hydroxyapatite is a calcium phosphate compound that can be synthesized from natural ingredients with calcium content such as coral reefs. Coral reefs are marine biota with a CaCO3 content of 98.8%. This study aims to synthesize hydroxyapatite through the formation of Precipitated Calcium Carbonate (PCC) from coral reefs. The research procedure begins with the calcination process of coral reefs to form CaO which is then made into PCC using the carbonation method. PCC as a source of calcium is synthesized into hydroxyapatite using the precipitation process with variations in pH (9 and 11) and sintering temperature (without sintering, 400oC, 500oC, 600oC). The synthesized hydroxyapatite was analyzed by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The results of the XRD analysis showed the formation of hydroxyapatite compounds from the angle 2θ which corresponds to the data (ICDD 01-072-1243). Hydroxyapatite synthesized at pH 11 and sintering temperature of 600oC gave the best results with hexagonal crystal structure, the value of the degree of crystallinity was 89,632 and the crystal size was 18,0623. Keywords: degree of crystallinity, PCC, pH, sintering temperature